Kontribusi Pembibitan Bambu Terdahap Pendapatan Keluarga di Kelompok wanita Tani Wonga Walu - Oktaviana Yohana Klau; Maria M. E. Purnama; Pamona S. Sinaga; Astin E. Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2026)
Bamboo cultivation through seedling to overcome the problem of bamboo availability is very beneficial for the community in improving family opinions. This study aims to determine the contribution of bamboo nurseries to increasing family income by mothers in the Wonga Walu Farmer Women's Group. This research was conducted in Turekalisa Village, West Golewa District, Ngada Regency in July-August 2023. The data collection technique in this study used census techniques. Then the data that has been collected is analyzed using descriptive analysis and quantitative analysis and to measure household income using the Yrt = Yi1 + Yi2. The results showed that income from the main job ranged from Rp 200,000-700,000 / month with a total of Rp 48,600,000 / year. While the side income from the sale of bamboo seeds is Rp 52,500,000 / year from three sales in a year. From the total main income and side income from the sale of bamboo seeds, the Wonga Walu Farmer Women group can generate IDR 101,100,000 / year with a percentage of 51.92%.